Innovative millimetre‐wave resonators based on slow‐wave coplanar stripline components. Issue 7 (4th May 2022) - Saadi, Abdelhalim A.; Margalef‐Rovira, Marc; Amara, Youcef; Vincent, Loïc; Lepilliet, Sylvie; Gaquiere, Christophe; Ferrari, Philippe
Abstract: In this paper, the slow‐wave coplanar stripline (S‐CPS) technology is utilised to design high performance and small footprint resonators operating within the millimetre‐wave band from 50 to 80 GHz. The proposed resonators are designed based on high quality factor quasi‐lumped capacitances and inductances offering a great flexibility in terms of design. The derivation of these components from the S‐CPS is explained theoretically and their behaviour is validated by EM simulation; an equivalent electrical model is also developed. The proposed concepts are demonstrated in the BiCMOS 55‐nm technology, and a good agreement between modelling, EM simulation and measurement results is achieved. The proposed devices could later be considered as interesting elementary blocks for the design of mm‐wave filters.